Advance of Clustered Regularly Interspaced Short Palindromic Repeats-Cas9 System and Its Application in Crop Improvement - Rao, Yuchun; Yang, Xi; Pan, Chenyang; Wang, Chun; Wang, Kejian (Frontiers in Plant Science, 2022)
CRISPR-Cas9 is the third generation of novel targeted genome editing technology after ZFNs (Zinc finger nucleases) and TALENs (Transcription activator like effector nucleases). It is also one of the most promising techniques for mutating and modifying genes. The CRISPR-Cas9 system has the advantages of simplicity, high efficiency, high specificity and low production cost, thus greatly promoting the study of gene function. Meanwhile, it has attracted the attention of biologists. After the development and improvement in recent years, CRISPR-Cas9 system has become increasingly mature and has been widely used in crop improvement. Firstly, this review systematically summarizes the generation and advantages of CRISPR-Cas9 system. Secondly, this review focuses on the application of CRISPR-Cas9 system in gene knockout, gene knock-in and gene regulation, as well as the improvement of yield, quality and biological resistance of important crops such as rice, wheat, soybean, corn and potato. Finally, this review proposes the potential challenges of CRISPR-Cas9 system, and discusses the future development of CRISPR-Cas9 system.